Motor and Sensory Impairments of the Lower Extremities After L2 Nerve Root Transection During Total en Bloc Spondylectomy. Issue 16 (15th August 2019) - Kato, Satoshi; Murakami, Hideki; Demura, Satoru; Ota, Takashi; Takahashi, Naoki; Yoshioka, Katsuhito; Shinmura, Kazuya; Yokogawa, Noriaki; Kawahara, Norio; Tomita, Katsuro; Tsuchiya, Hiroyuki
Abstract : Study Design: Retrospective study. Objective: The purpose of this study was to examine motor and sensory impairments of the lower extremities after L2 nerve root transection during total en bloc spondylectomy (TES) for spinal tumors. Summary of Background Data: At our institute, for TES at L3 to L5 lumbar levels, the nerve roots are preserved. However, at the level of L1 and L2, the vertebral resection and spinal reconstruction via a posterior approach is employed with transection of the nerve roots during dissection and resection of the vertebra. Methods: This study included 13 patients who had undergone TES for spinal tumors involving L2 between 2007 and 2016. Postoperative motor function of the lower extremities was quantified using the Manual Muscle Testing grade for the iliopsoas (IP) and quadriceps femoris (QF) muscles, and a grade of the modified Frankel Classification. Postoperative sensory impairment was quantified by the sites of lower extremity pain and numbness. Results: An initial decrease in strength of the IP and QF muscles in more than 60% of the patients, with a decline in the modified Frankel grade in 76.9%, was observed at 1-week after surgery. All patients recovered by the final follow-up, with 12 of the 13 patients walking without a gait aid. The other patient, who had undergone a bilateral dissection of L3 nerve root during TES of L2 and L3, had a mild QF muscle weakness, requiring a cane for walking. Eleven of 13 patients developed pain or numbness in the groin or thigh area after surgery, with the most common area being the anterior aspect of the thigh. Conclusion: Although IP and QF weakness was observed in the majority of patients who underwent bilateral transection of L2 nerve roots during TES, these deficits recovered over time and did not finally affect activities of daily living. Level of Evidence: 4 Abstract : An initial weakness of the iliopsoas and quadriceps femoris muscles was observed in the majority of patients who underwent bilateral transection of L2 nerve roots during total en bloc spondylectomy for spinal tumor involving L2. However, these deficits recovered over time and did not finally affect activities of daily living.